Effect of low-dose esketamine on cardio-biliary reflex and postoperative pain during laparoscopic cholecystectomy surgery: A randomized, controlled trail - Xiaodong Zhang; Peng Duan; Yingjie Sun; Qi Na (PLoS ONE, 2025)
Background Cardio-biliary reflex can lead to cardiac arrest, brady-arrhythmia, cardiogenic shock, and other severe complications. NMDA receptor antagonists have been shown to have the effect of anti-vagal reflex. However, the regulation of vagus reflex by esketamine, an NMDA receptor antagonist, remains unclear. Our study aims to investigate intravenous low-dose esketamine on cardio-biliary reflex. Methods In this randomized controlled trial, adult patients undergoing laparoscopic cholecystectomy were allocated in a 1:1 ratio to esketamine group or control group. 5 minutes before surgical incision, participants in the esketamine group received 0.3 mg/kg of esketamine, while the control group received an equivalent volume of normal saline. The primary outcome was the occurrence of cardio-biliary reflex. Postoperative pain was assessed using the Visual Analogue Scale (VAS) on days 1, 2, and 3 post-surgery. Results Our final analysis included 140 participants. The incidence of the cardio-biliary reflex occurred in 15 patients (21.4%) in the control group compared with 6 patients (8.6%) in the esketamine group (relative risk 0.34; 95%confidence interval (95% CI): 0.125–0.947; P < 0.05). Patients in the esketamine group reported lower pain intensity with movement on postoperative days (POD)1, 2, and 3 with mean differences (MD) of 0.59, 0.70, and 0.47 points respectively (all P < 0.05). Additionally, pain intensity at rest was also lower in the esketamine group at all observation time points (POD1: MD 0.51, POD2: MD 0.40, POD3: MD 0.30, all P < 0.05). Conclusions Therapeutic use of low-dose esketamine significantly reduces the occurrence of cardio-biliary reflex and postoperative pain in patients undergoing laparoscopic cholecystectomy.